Designing a Contact Fingertip Sensor Made Using a Soft 3d Printing Technique - Melo-Hurtado, F; Ibarra-Orellana, A (MARY ANN LIEBERT, INC, 2022)
The development of highly compliant materials and actuators has enabled the design of soft robots that can be applied in rescue operations, in secure human-robot interactions, to manipulate fragile devices or objects, and for robot locomotion within complex environments. To develop reliable solutions for soft robotics applications, devices with the ability to deform and change shape are required, which must be equipped with appropriate sensors capable of withstanding large deformations at suitable speeds and respond repeatedly. This work presents a methodology to build strain sensors made of sensitive, thin, and conductive channels printed inside a soft matrix, using three-dimensional printing. As proof of concept, rectangular beams and semispherical caps embedded with sensitive circuits are developed that are designed to deform under applied forces and detect the gradual contact with objects. The rectangular beam with conductive lines separated from the neutral plane exhibits a quasi-linear electrical response as a function of the applied shear strain. Mechanical diodes, which trigger an activated response once a given deformation onset is exceeded, are implemented using circumferential conductive channels that are centered with the spherical body sensor. Sinusoidally shaped conductive channels located at a given distance from the spherical surface produce a monotonic electrical response, which detects deformations over a broad range. Linear sensors, with enhanced sensitivity to compression, are created if the sensitive conductive channels are oriented along the compression direction. Numerical calculations, used to guide the design of the sensor, show the capability of these sensors to measure simultaneous normal and tangential forces, making them suitable for applications involving fragile object manipulation and robot locomotion. An example of application of these sensors in the control of the forces applied by soft gripper lifting an object is given.